Pathogenic Old World arenaviruses inhibit TLR2/Mal-dependent proinflammatory cytokines in vitro - Hayes, Melissa W; Carrion, Jr, Ricardo; Nunneley, Jerritt; Medvedev, Andrei E; Salvato, Maria S; Lukashevich, Igor S (Journal of virology, 2012)
Lymphocytic choriomeningitis virus (LCMV), the prototype arenavirus, and Lassa virus (LASV), the causative agent of Lassa fever (LF), have extensive strain diversity and significant variations in pathogenicity for humans and experimental animals. The WE strain of LCMV (LCMV-WE), but not the Armstrong (Arm) strain, induces a fatal LF-like disease in rhesus macaques. We also demonstrated that LASV infection of human macrophages and endothelial cells resulted in reduced levels of proinflammatory cytokines. Here we have shown that cells infected with LASV or with LCMV-WE suppressed Toll-like receptor 2 (TLR2)-dependent proinflammatory cytokine responses. The persisting isolate LCMV clone 13 (CL13) also failed to stimulate interleukin-6 (IL-6) in macrophages. In contrast, nonpathogenic Mopeia virus, which is a genetic relative of LASV and LCMV-Arm induced robust responses that were TLR2/Mal dependent, required virus replication, and were enhanced by CD14. Superinfection experiments demonstrated that the WE strain of LCMV inhibited the Arm-mediated IL-8 response during the early stage of infection. In cells transfected with the NF-κB-luciferase reporter, infection with LCMV-Arm resulted in the induction of NF-κB, but cells infected with LCMV-WE and CL13 did not. These results suggest that pathogenic arenaviruses suppress NF-κB-mediated proinflammatory cytokine responses in infected cells.